2008
DOI: 10.3892/ijo.32.3.689
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharopeptide enhances the anticancer activity of doxorubicin and etoposide on human breast cancer cells ZR-75-30

Abstract: In search of natural bioactive microbial compounds with adjuvant properties, we have previously showed that the polysaccharopeptide (PSP), isolated from Chinese medicinal mushroom Coriolus versicolor, was able to enhance the cytotoxicity of certain S-phase targeted-drugs on human leukemic HL-60 cells via some cell-cycle and apoptotic-dependent pathways. The present study aimed to investigate whether the synergism of mechanisms of PSP with certain chemotherapeutic drugs also applies to human breast cancer. PSP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 53 publications
(86 reference statements)
0
34
0
Order By: Relevance
“…The cell cycle kinetics analysis was achieved by using the bivariate BrdUrd/DNA flow cytometry technique as previously described by our group (24) and other investigators (25)(26)(27). The method is based on simultaneous measurement of the total incorporation or the rate of incorporation of the thymidine analog, BrdUrd, into newly synthesized DNA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cell cycle kinetics analysis was achieved by using the bivariate BrdUrd/DNA flow cytometry technique as previously described by our group (24) and other investigators (25)(26)(27). The method is based on simultaneous measurement of the total incorporation or the rate of incorporation of the thymidine analog, BrdUrd, into newly synthesized DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Staining of cells for bivariate analysis of BrdUrd/ DNA flow cytometry analysis was performed as previously described by our group (24). Prior to staining of 2x10 6 BrdUrd incorporated cells, fixative was removed by washing twice with PBS and the DNA of cells were partially denatured by incubation with 2 M HCl for 20 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have demonstrated that polysaccharides from basidiomycetes mushrooms had highly beneficial therapeutic effects including: i) preventing oncogenesis after the administration of peroral medications developed these mushrooms or their extracts, ii) direct anti-tumor activity against various tumors, iii) synergistic anti-tumor activity in combination with chemotherapy, and iv) preventive effects on tumor metastasis (13)(14)(15)(16). Data on polysaccharides isolated from Agaricus blazei Murill (ABM) are highly impressive, and these polysaccharides show promise for use as cancer therapeutics.…”
Section: Introductionmentioning
confidence: 99%